Institutional Architecture of Regional Payment Unions as Alternatives to SWIFT and the IMF - Chopenko, Darya (Актуальні питання економічних наук, 2026)
The relevance of this study is driven by the transformation of the global monetary and financial system, increasing geoeconomic fragmentation, asymmetries in financial sovereignty, and the growing role of institutional constraints in international settlements. Under the dominance of centralized global payment infrastructures and supranational stabilization mechanisms, there is an increasing need to develop regional institutional alternatives capable of strengthening payment autonomy and financial resilience of participants without full isolation from the international financial system. The purpose of the article is to identify and provide a scientific justification for the basic institutional parameters of regional payment unions as alternative or complementary mechanisms to SWIFT and the IMF in the context of structural changes in global monetary and financial architecture. The research methods are based on institutional analysis, a structural and functional approach, comparative analysis, and logical-analytical generalization, which made it possible to systematize the functions, structural elements, and constraints of regional payment unions in the context of international monetary and financial relations. The results show that regional payment unions are institutionalized mechanisms for the multilevel organization of cross-border settlements that combine payment, coordination, and stabilization functions. Their effectiveness is determined not so much by technical characteristics as by the coherence of institutional architecture, a clear distribution of mandates, the availability of liquidity management mechanisms, and regulatory compatibility among participants. Key challenges in the formation and functioning of such unions were identified, including institutional asymmetry, regulatory fragmentation, coordination costs, and the limited resource base of stabilization instruments. The conclusions indicate that regional payment unions are not a full substitute for global payment networks and supranational financial institutions; however, they function as an institutional buffer that enhances payment autonomy and reduces the financial vulnerability of participants within a regional system.